ANALISIS PROSES BERPIKIR KREATIF SISWA KINESTETIK DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN TAHAPAN WALLAS - Setiawani, Susi; Syafitriyah, Dini; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research is aimed to describe the creative thinking process of kinesthetic students in solving Mathematics problems based on Wallas Stage. The type of this research is descriptive research with qualitative approach. Data collection method used in this research is questionnaire, test, and interview. The research participants were 8 student's kinesthetic learning style on the X grade of Tissue Culture Cultivation Department of SMK Negeri 5 Jember. Based on Wallas Stage, creative thinking is classified into 4 stages, preparation, incubation, illumination, and verification. The result of the research shows that kinesthetic learning style of student's creative thinking process is different, the student passed creative thinking stage as proposed by Wallas. Student of kinesthetic learning style shows the same behavior in passing preparation stage, they are able to dig up the beginning information in the task, in illumination stage students gain the inspiration to solve, in incubation stage there were 5 students who distract the attention by trying to write in blur paper and 3 students distract the attention by pausing for a moment and doing nothing, in verification stage there are 7 students that shows the same behavior which is rechecking problem solving to the reality and one student did not pass the verification stage. Keywords: Creative thinking based on Wallas Stage, Kinesthetic Learning Style, Problem Solving